1977
DOI: 10.1056/nejm197710132971504
|View full text |Cite
|
Sign up to set email alerts
|

Lassa Fever: Response to an Imported Case

Abstract: In February, 1976, a Peace Corps worker returned to the United States from Sierra Leone with an undiagnosed illness later recognized as Lassa fever. To assess the risk of transmission and to contain a potential outbreak, we identified 552 contacts as having had exposure to the patient before the start of strict isolation procedures, and maintained intensive surveillance on these contacts for 21 days. At the end of the surveillance period, no illness had developed in contacts. One month later, a serologic surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…This is in agreement with the findings of previous studies, which have not detected secondary transmissions by surveillance and serological testing of selected contacts [4][5][6]. In contrast to these investigations, a probable transmission was identified in a person who had a close contact on day 9 of illness.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the findings of previous studies, which have not detected secondary transmissions by surveillance and serological testing of selected contacts [4][5][6]. In contrast to these investigations, a probable transmission was identified in a person who had a close contact on day 9 of illness.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Investigations to assess the risk of secondary infection were undertaken in cases of Lassa fever imported into the United States and Great Britain [4][5][6]. No clinically apparent secondary cases were observed, and serological testing of a subgroup of contacts revealed no asymptomatic infections.…”
mentioning
confidence: 99%
“…These results are consistent with those of previous studies, which showed a low risk for person-to-person transmission in hospital settings ( 6 , 9 – 11 , 13 , 17 ). In countries to which LASV is not endemic, ≈40 cases of imported Lassa fever have been reported since LASV was first identified in 1969, and only 1 case of secondary transmission in this type of country has been reported ( 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…In countries to which LASV is not endemic, risk for nosocomial transmission has been reported to be low in persons caring for the hospitalized index patient, even without more special precautions than barrier nursing methods ( 9 12 ). Serologic studies in these countries have not demonstrated nosocomial transmission resulting in infections in healthcare workers ( 9 , 10 , 13 ). …”
mentioning
confidence: 99%
“…In the past, heroic efforts have been made to trace fellow travellers across international boundaries, such as following the importation of Lassa fever to the USA, with no evidence of transmission in several hundred potential contacts [21]. Within endemic areas, close family contact (in addition to the preparation of bodies for burial) has been implicated in the transmission of most VHFs originating in Africa, but this has only been documented in Western settings for Marburg infection transmitted sexually to a female spouse, and in South America for Argentinean haemorrhagic fever [4] and Andes HPS virus [122].…”
Section: Risks For Fellow Travellers and Family Contactsmentioning
confidence: 99%